Going viral: A scoping review of the current state and impact of online research dissemination in emergency medicine. Issue 1 (18th February 2022) - Gray, James M.; Schnadower, David; LaFollette, Ryan; Shah, Ashish S.; Sobolewski, Brad
Abstract: Background: The use of free open‐access medical education (FOAM) and other online knowledge dissemination methods has increased over the past decade. However, the role and impact of these tools in the knowledge translation continuum are poorly understood, potentially limiting the ability of knowledge generators to fully harness and exploit their potential. Here, we aim to comprehensively map and synthesize the literature describing the use of online tools for the dissemination of emergency medicine research. Methods: Using scoping review methodology, we searched the traditional literature via PubMed, CINAHL, EMBASE, ERIC, SCOPUS, and the gray literature for publications exploring online methods to disseminate new research findings. We synthesized the results and constructed a conceptual model of current research dissemination methods. Results: We included 79 out of 655 unique abstracts and articles identified in our search, 62 of which were from the traditional literature. We describe six primary domains: integration with traditional literature, measurement of dissemination, online organizations and communities of practice, professional development, quality assurance tools and techniques, and advantages and disadvantages of FOAM. For each domain we present an exemplar article and prevailing gaps in knowledge. Finally, we propose a current conceptual framework for dissemination of new research findings that describes both traditional and novel methods of dissemination. Conclusions: This comprehensive review of the literature and current dissemination framework will empower researchers, research networks, and granting organizations to maximize their use of FOAM and other online methods to disseminate new knowledge as well as provide clinicians a better understanding of the tools and methods by which to access and implement new research findings.